MO292MALIGNANT DISEASE IS MORE COMMON WITH DETERIORATING KIDNEY FUNCTION IN PATIENTS WITH MEMBRANOUS NEPHROPATHY. (29th May 2021) - Vukovic Brinar, Ivana; Kurtov, Karlo; Laganovic, Mario; Dika, Zivka; Ćorić, Marijana; Gellineo, Lana; Fistrek Prlic, Margareta; Jelakovic, Bojan
Abstract: Background and Aims: Membranous nephropathy (MN) can be associated with tumor and present a paraneoplastic condition. Recently, development of tumors during the course of follow up is more in focus. It is especially interested whether patient with MN are prone to tumors, or tumors are condition indipendent of membranous nephropathy or consequence of imunosupressive therapy (IS). Method: Retrospective data of all adult patients diagnosed with MN from 1987 to 2017 at the Department of Nephrology of University Hospital Centre Zagreb were analysed. Medical data regarding antropometric measeures and preexsisting comorbid disease at presentation and during follow up were derived from medical records and hospital informatic system. Furthermore, data regarding kidney function were used, namely serum creatinine (SCr), proteinuria. Renal function was assessed using CKD-EPI equation. CKD stages, partial and complete remission were defined according to KDIGO guidelines. Results: From 1987 till 2017 a total of 122 patients were diagnosed with MN. Eighty nine (72.9%) were treated with imunosupressive therapy. Most commonly prescribed initial therapy was combination of corticosteroids and cyclophosphamide (N=66; 74%). Three (0, 02%) patients had history of tumor with median of 3y (min – max 1-4 y) before glomerular disease presentation, two solid tumor, adenocarcinoma pulmonum and carcinoma prostatae, and one condition after allogenic haematopoetic transplantation due to acute myeloid leukemia. There was no difference in clinical presentation between those with positive history of malignant disease and others (proteinura 11.7 g/du (25-75C 3.4-15.7) vs. 5.8 g/dU (25-75C 3.4 – 8.5); p=0.232 and eGFR 57 ml/min/1, 73m 2 (25C-75C 14 – 59) vs. 81 ml/min/1.73m2 (25-75C 54 – 100); p=0.066). During follow up 11 (9%) patients developed tumor, median age of pts 67 y (min – max 59 – 71); nine solid tumors most comonly of gastrointestinal origin (pancreas, colon N=5 (45%)), then pulmonum (N=2(18%)) and urogenithal origin (ca renis and prostate N=2 18%). Also two hematological malignancies (B-ALL, B-NHL) occurred. Median time till confirmed malignant disease was 9 y (min – max 5 -24). At the time of detecting the tumor six (54%) patients were in complete and partial remission (4 and 2) and 2 (18%) patients had nephrotic syndrome. No difference was observed in proteinuria between those with malignant condition and other MN patients (1, 4 g/dU (25 – 75C 0.2 – 5.6) vs. 0, 29 g/dU (25 – 75C 0.13 – 0.74); P=0.154). MN patients with malignant disease during follow up had lower estimated glomerular filtration rate (eGFR 45 ml/min/1, 73m 2 (25 – 75C 22 – 70) vs. 77 (25 – 75C 58 – 92); p=0.010). There was no difference in cummulative dose of cyclophosphamide between those who developed tumor with others (24 g(25 – 75C13.5 – 30) vs. 27 g(25 – 75C 15 – 38)p=0.592). Conclusion: Our data emphasize the need for long term follow up of patients with membranous nephropathy despite accomplishing remission of MN and period screening for malignant disease, especially in those with deteriorating kidney function.